Biomimetic hydrogen-bonding cascade for chemical activation: telling a nucleophile from a base. Issue 2 (10th November 2020) - Park, Hyunchang; Lee, Dongwhan
Abstract : Biomimetic cascade hydrogen bonds promote covalent capture of a nucleophile by polarizing the electrophilic reaction site, while suppressing non-productive acid–base chemistry as the competing reaction pathway. Abstract : Hydrogen bonding-assisted polarization is an effective strategy to promote bond-making and bond-breaking chemical reactions. Taking inspiration from the catalytic triad of serine protease active sites, we have devised a conformationally well-defined benzimidazole platform that can be systematically functionalized to install multiple hydrogen bonding donor (HBD) and acceptor (HBA) pairs in a serial fashion. We found that an increasing number of interdependent and mutually reinforcing HBD–HBA contacts facilitate the bond-forming reaction of a fluorescence-quenching aldehyde group with the cyanide ion, while suppressing the undesired Brønsted acid–base reaction. The most advanced system, evolved through iterative rule-finding studies, reacts rapidly and selectively with CN − to produce a large (>180-fold) enhancement in the fluorescence intensity at λ max = 450 nm.